MODAL INTELEKTUAL PADA PERUSAHAAN-PERUSAHAAN DI SEKTOR KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2014 (Jurnal Ekonomi dan Kebijakan Pembangunan, 2017)
This study aimed to analyze the company's intellectual capital in the financial sector. The financial sector companies listed in the Indonesian Stock Exchange (BEI) 2010-2014 was used as the sample. The sample selection using purposive sampling method. The data used in this study were secondary data from company annual report obtained from the official website of Indonesia Stock Exchange. Measurement of intellectual capital in this study using a model of Value Added Intellectual Coefficients (VAIC) and measurement of financial performance using ratio analysis with ROA as profitability variable, ATO as productivity variable, and GR as variable growth. The results showed that the overall financial performance of the financial sector in the period of observation were top performers and common performers. Based on the value of company’s intellectual capital, the intellectual capital components contributed most was human capital. Keywords: Finance, Intellectual capital, Value added intellectual coefficient, VAIC